Optimizing battery discharge and charge strategies for enhanced Microgrid performance - Almihat, Mohamed G Moh; Munda, Josiah Lange (Edelweiss Applied Science and Technology, 2026)
This study aims to enhance the technical, economic, and environmental performance of hybrid microgrids (MGs) through optimal battery charging and discharging decisions. A simulation-based design integrating photovoltaic generation, battery energy storage, and diesel backup was used to evaluate multiple control strategies under identical operating conditions. A multi-objective optimization model based on the NSGA-II algorithm minimized total lifecycle cost and carbon emissions while ensuring operational resilience. The findings revealed that optimized scheduling is highly effective in enhancing renewable use, stabilizing battery state-of-charge, and virtually eliminating the need for diesel generators, resulting in over 90% cost reduction and minimal emission penalties. The optimized system showed improved net load profiles, longer battery life, and greater robustness compared to non-optimized operation. The study concludes that a battery-centric, intelligent control, and component-sizing approach is superior to renewable oversizing for the sustainability of MGs. Practically, the results show that innovative energy management can enable resilient, low-carbon, and cost-effective MG operations without increasing renewable capacity.